Youths, news and COVID-19: a media dependency study on 18-21-year-olds in Malaysia - Gomez, Lydia Edwina (2021)
Between March 17 and May 4, 2020, Malaysia announced four phases c of an unprecedented nationwide movement restriction - the Movement Control Order (MCO) - to prevent the spread of the COVID-19 virus. As a consequence, civil society was confined to their homes while the Malaysian Ministry of Health (MoH) provided daily updates and hyper-localized information through the media and their own social media channels.